Strategi Transformasi Penyuluhan Pertanian melalui Teknologi Digital: Literature Review - Iwan Patria (Yayasan Literasi Sains Indonesia, 2025)
Agricultural extension plays a crucial role in enhancing farmers’ capacity, accelerating the adoption of innovations, and supporting sustainable agricultural development. The utilization of digital technology in agricultural extension has emerged as a key strategy to enhance farmers’ capacity, expand information access, and support sustainable agricultural development. Seven recent studies (2021–2025) were analyzed, covering the use of mobile applications, web-based information systems, social media, and Internet of Things (IoT) to strengthen agricultural extension. Findings reveal that digital tools enhance communication reach, accelerate innovation adoption, and contribute to improved productivity and crop quality. Nevertheless, challenges persist, including inadequate rural internet infrastructure, neutral or resistant farmer attitudes toward digital adoption, and the limited integration of information systems across institutions. To overcome these barriers, comprehensive strategies are required: (1) enhancing digital literacy among farmers and extension agents through participatory learning, (2) strengthening rural digital infrastructure via cross-sector collaboration, (3) repositioning extension agents as innovation catalysts in line with the vision of Society 5.0, and (4) developing integrated data-driven systems supported by big data analytics and GIS. Theoretically, this study contributes to the development of a conceptual framework for digital agricultural extension as a socio-technical system, while practically it offers policy recommendations to build an inclusive, adaptive, and sustainable extension system. Ultimately, digital transformation in agricultural extension is not only vital for accelerating innovation diffusion but also plays a strategic role in reinforcing Indonesia’s national food security and supporting sustainable rural development.